Legal certainty regarding online legal consultation regulations by advocates - Taufan, Ridwan Anthony; Barthos, Megawati (Indonesian Journal of Multidisciplinary Science, 2024)
The legal landscape surrounding online legal consultations in Indonesia is complex. This research aims to analyze the legal certainty surrounding the regulation of online legal consults by advocates in Indonesia, contributing significantly to the understanding of the existing legal framework governing these services. Thematic analysis was employed to identify key themes and patterns related to the legal and ethical challenges faced in practice. The findings provide guidance for policymakers on the need for clearer regulations, which could enhance standards and protections for both advocates and clients. Increasing advocates' knowledge about the regulations and ethics of online consultations, developing secure platforms, and clearly promoting legal services to the public are essential steps to create trust and enhance public participation in utilizing these services, while also laying the groundwork for future studies on related topics.